Rectal avulsion associated with complex open pelvic fracture following rollover injury. (April 2023) - Ping Jen, Jian; Addison, Sarah; Amerasekera, Steve
Background: We present a rare case of complete rectal avulsion from the external anal sphincter complex associated with unstable pelvic ring disruption, including spinopelvic dissociation, following rollover by tractor. In the context of major pelvic trauma, evaluating for unstable bony, acute vascular, urethral and bladder injuries is essential. However, a detailed search for anorectal injury is also required by the reporting radiologist.Case Report: In this case report we highlight specific pelvic floor anatomy on CT, with a focus on gross morphology and the presence of peri-rectal free gas as primary evidence for injury. Secondary radiological evidence which should trigger the search for anorectal injury includes bony posterior pelvic ring disruption (sacrum or coccyx fractures) or associated Morel-Lavallee lesions.Conclusion: The presence of radiological abnormality should prompt direct clinical inspection for corroboration. Early recognition is crucial for joint colorectal and orthopaedic management and the avoidance of delayed pelvic sepsis, which may become intractable.